ISC2 CISSP Certified Information Systems Security Professional Official Practice Tests - Chapple, Mike 1975-; Seidl, David (John Wiley & Sons, Inc., 2024)
Full-length practice tests covering all CISSP domains for the ultimate CISSP prep The ISC2 CISSP Official Practice Tests is a major resource for ISC2 Certified Information Systems Security Professional (CISSP) candidates, providing 1300 unique practice questions. The first part of the book provides 100 questions per domain. You also have access to four unique 125-question practice exams to help you master the material. As the only official practice tests endorsed by ISC2, this book gives you the advantage of full and complete preparation. These practice tests align with the 2024 version of the CISSP Detailed Content Outline to ensure up-to-date preparation, and are designed to cover what you will see on exam day. Coverage includes: Security and Risk Management, Asset Security, Security Architecture and Engineering, Communication and Network Security, Identity and Access Management (IAM), Security Assessment and Testing, Security Operations, and Software Development Security. The CISSP credential signifies a body of knowledge and a set of guaranteed skills that put you in demand in the marketplace. This book is your ticket to achieving this prestigious certification, by helping you test what you know against what you need to know. Test your knowledge of the 2024 CISSP domains Identify areas in need of further study Gauge your progress throughout your study and preparation Practice test taking with Sybex's online test environment containing the questions from the book The CISSP objectives are refreshed every few years to ensure that candidates are up-to-date on the latest security topics and trends. Currently-aligned preparation resources are critical, and periodic practice tests are one of the best ways to truly measure your level of understanding.
Description based on online resource; title from digital title page (viewed on June 24, 2024)
Keywords: Computer security -- Examinations, questions, etc; Sécurité informatique; Examens, questions, etc